Penggunaan Alef Education untuk pembelajaran keterampilan menyimak di Madrasah Tsanawiyah 4 Pasuruan - Rizqiyah, Naila Mazidah (Maliki Interdisciplinary Journal, 2024)
This research aims to: 1) To describe the use of Alef Education in listening skill learning at Islamic State Junior High School Four of Pasuruan, 2) To measure the effectiveness of using Alef Education in listening skill learning at Islamic State Junior High School Four of Pasuruan. This research uses a quantitative approach with an experimental method with a Quasi Experimental Design type. The results of the research can be concluded that: 1) media use can be done in several stages, namely registering an Alef Education account, then using Alef Education media to learn Arabic. This media is easy to use in learning listening skill because it is interesting and not boring, this is proven by the questionnaire results of 79.57%. 2) The research results showed that the pretest score was an average of 48.93 and after being applied using the Alef Education media the posttest score was produced with an average of 87.14 and it was known from the results of the Independent Sample T-Test which showed a Sig. 2-tailed = 0.000 < 0.05. Thus, Ha is accepted and H0 is rejected. From these data it can be concluded that the use of Alef Education media is effective in learning listening skill at Islamic State Junior High School Four of Pasuruan.